The challenges with inter-disciplinary collaboration in value-chain research - Kawarazuka, Nozomi (International Potato Center, 2019)
Presented by Nozomi Kawarazuka (International Potato Center), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.